Correlates of Online Transport Drivers’ Service Literacy: Service Resilience, Organizational Citizenship Behavior, and Sensation-Seeking - Madeline Jessica; Juneman Abraham (ANIMA Indonesian Psychological Journal, 2019)
Besides being of benefit, online transport services in Indonesia also receive complaints from customers. It is not surprising that online transport service businesses have striven to improve their services by introducing electronic features, which are hoped to be able to improve feelings of being safe and comfortable, amongst users. This research assumes that the increases in electronic features are necessary, but insufficient. These features need to be supplemented by the service literacy of the driver/riders. The goal of this research is to attempt to test correlational hypotheses concerning the relationships between the three psychological variables, service resilience, organizational citizenship behavior and sensation-seeking; and service literacy. The research, conducted with 272 driver/riders (255 males, 17 females; Mage = 32.8 years old, SDage = 8.028 years) of online motorcycle taxis (ojek), indicated that those hypotheses were supported by empirical data.